Targeted Extracellular Vesicle Gene Therapy for Modulating Alpha-Synuclein Expression in Gut and Spinal Cord - Maria Izco; Martin Schleef; Marco Schmeer; Estefania Carlos; Guglielmo Verona; Lydia Alvarez-Erviti (Pharmaceutics, 2023)
The development of effective disease-modifying therapies to halt Parkinson’s disease (PD) progression is required. In a subtype of PD patients, alpha-synuclein pathology may start in the enteric nervous system (ENS) or autonomic peripheral nervous system. Consequently, strategies to decrease the expression of alpha-synuclein in the ENS will be an approach to prevent PD progression at pre-clinical stages in these patients. In the present study, we aimed to assess if anti-alpha-synuclein shRNA-minicircles (MC) delivered by RVG-extracellular vesicles (RVG-EV) could downregulate alpha-synuclein expression in the intestine and spinal cord. RVG-EV containing shRNA-MC were injected intravenously in a PD mouse model, and alpha-synuclein downregulation was evaluated by qPCR and Western blot in the cord and distal intestine. Our results confirmed the downregulation of alpha-synuclein in the intestine and spinal cord of mice treated with the therapy. We demonstrated that the treatment with anti-alpha-synuclein shRNA-MC RVG-EV after the development of pathology is effective to downregulate alpha-synuclein expression in the brain as well as in the intestine and spinal cord. Moreover, we confirmed that a multidose treatment is necessary to maintain downregulation for long-term treatments. Our results support the potential use of anti-alpha-synuclein shRNA-MC RVG-EV as a therapy to delay or halt PD pathology progression.